BENEFITS AND HARMS OF THERAPEUTIC HYPOTHERMIA IN NEONATES WITH HYPOXEMIC BRAIN DAMAGES (CIPEEX, 2022)
THERAPEUTIC HYPOTHERMIA IS USED AS A TREATMENT WITH THE INTENTION OF REDUCING MORTALITY AND NEUROLOGICAL SEQUELAE IN NEONATES WITH RESPIRATORY HYPOXEMIC DAMAGE.&NBSP; THUS, THIS STUDY SOUGHT TO DESCRIBE THE BENEFITS AND HARMS FOR NEWBORNS ADMITTED TO THIS TREATMENT OBJECTIVE: TO IDENTIFY THE BENEFITS AND HARMS OF THERAPEUTIC HYPOTHERMIA IN NEWBORNS WITH HYPOXIC-ISCHEMIC ENCEPHALOPATHY.
Keywords: therapeutic hypothermia; newborn; ypoxic-ischemic encephalopathy